Treat a Cop Like They Are God: Exploring the Relevance and Utility of Funds of Gang Knowledge Among Latino Male Students. (October 2021) - Huerta, Adrian H.; Rios-Aguilar, Cecilia
Latinos represent 20% of the more than 1 million gang-associated youth in the United States. This study explores how gang associated Latino males use their funds of gang knowledge to navigate their urban schools and communities. The findings highlight how Latino males build relationships and exchange information with each other, endure and persevere during juvenile incarceration, how youth interact with law enforcement, and how youth advance their status in gangs. Educators must learn how to anticipate and support gang-associated Latino males to understand their social worlds they bring into schools.